Urban River Interventions in São Paulo Municipality (Brazil): The Challenge of Ensuring Justice in Sociotechnical Transitions - Travassos, Luciana; Momm, Sandra (Frontiers in Sustainable Cities, 2022)
The paper aims to discuss the sociotechnical transitions regarding urban rivers policy in São Paulo Municipality by focusing on programs and projects conducted since 2000. Accordingly, we use a theoretical reflection on sociotechnical transitions and just transitions in interventions related to water and cities. Our work is based on a documental analysis of programs and projects for urban rivers in the municipality conducted via theoretical discussion. The primary focus is on the current sociotechnical regime, the channeling of streams and construction of road systems on its banks, and disputes and pressures brought by the technological landscape and niches, which lead to the construction of linear parks and leisure areas along with the bodies of water. It also shows how the issue of justice has been losing ground in this transition, which although is “in the making,” already presents many factors of injustice. This is due to the low presence of the theme of precarious settlements, in innovative speeches and practices, and the different treatment given by the programs and projects for rivers in the consolidated middle- and upper-class regions and for those located on the peripheries.